1986
DOI: 10.1073/pnas.83.24.9556
|View full text |Cite
|
Sign up to set email alerts
|

2-(N-acetoxy-N-acetylamino)fluorene mutagenesis in mammalian cells: sequence-specific hot spot.

Abstract: Mutations induced by 2-(N-acetoxy-N-acetylamino)fluorene were studied using temperature-sensitive simian virus 40 (SV40) mutants as probe in monkey kidney cells. In vitro treatment of the SV40 virions with 2-(N-acetoxy-Nacetylamino)fluorene increased mutagenesis and decreased survival in the viral progeny. A lethal hit of approximately 85 acetylaminofluorene adducts per SV40 genome was calculated.UV irradiation of cells prior to infection did not modify the results. Molecular analysis of independent SV40 rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…These sites are included in restriction enzyme-recognizing sequences which could form small hairpin structures. We suggest that these structures may be involved in the observed spontaneous mutation hot spots already reported for some other secondary DNA structures (13,23,27). Indeed, one of the mutations (position 2533) is a silent one and therefore not responsible for the phenotypic reversion.…”
Section: Discussionsupporting
confidence: 53%
“…These sites are included in restriction enzyme-recognizing sequences which could form small hairpin structures. We suggest that these structures may be involved in the observed spontaneous mutation hot spots already reported for some other secondary DNA structures (13,23,27). Indeed, one of the mutations (position 2533) is a silent one and therefore not responsible for the phenotypic reversion.…”
Section: Discussionsupporting
confidence: 53%
“…Among these deletions were a number of -1 frameshifts that occurred in runs of dAs. Gentil et al (14) reported that reversion of a temperaturesensitive mutation in SV40, produced by N-AAAF treatment of the vector followed by replication in African green monkey kidney cells, was mainly due to base substitutions at A:T base pairs. Finally, Klein et al (15) found that mutations were not associated with a site-specifically positioned dG-AAF adduct in a repair-deficient human cell/ shuttle vector system.…”
mentioning
confidence: 99%
“…The latter hypothesis is supported by recent studies on the specific mutational changes needed to activate specific oncogenes (7,37,44). Therefore, we and others (3,4,8,9,11,12,14,21,22,30,32,40,41) have begun to study the specific kinds of mutations induced by carcinogens in mammalian cells.…”
mentioning
confidence: 99%